Pengembangan Alat Bantu Peroboh Sapi Qurban: Meningkatkan Efisiensi, Keamanan, dan Kualitas Penyembelihan Masyarakat di Desa Sorowako - Abdul Tahir; Sirama Sirama; Musakirawati Musakirawati; Jasman Jasman (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The sacrificial animal slaughtering activities in Sorowako Village have long faced challenges such as occupational accident risks, lack of attention to animal welfare, and potential meat quality degradation due to manual toppling methods. This community service aims to develop a cattle-toppling aid to improve the efficiency, safety, and quality of the slaughtering process. The method used was Research and Development (R&D) with a participatory approach, involving the Al-Ukhuwah Mosque Prosperity Council (DKM) and experienced butchers. The activity stages included needs analysis, design, prototype fabrication, as well as testing and evaluation. The result is a functional, sturdy, and user-friendly toppling device based on a hollow iron frame with a pulley system. Implementation during Eid al-Adha demonstrated significant improvements: safety for butchers and committee members increased drastically, the toppling process became faster and more humane, and meat quality and hygiene were better maintained due to minimized contamination and bruising. The tool was well received by the community and has become a tangible solution aligned with Islamic principles (taysir) and animal welfare standards. Further development and continuous training are recommended for optimal use of the tool.